The prognostic value of ERCCI and RRMI gene expression in completely resected non-small cell lung cancer: Tumor recurrence and overall survival - Apichat Tantraworasin (2018)
Background: The roles of excision repair cross-complementing group 1 gene (ERCC1) expression and ribonucleotide reductase subunit M1 gene (RRM1) expression in completely resected non-small cell lung cancer (NSCLC) are still debatable. Previous studies have shown that both genes affected the overall survival and outcomes of patients who received platinum-based chemotherapy; however, some studies did not show this correlation. The aim of this study was to evaluate the prognostic values of ERCC1 and RRM1 gene expression in predicting tumor recurrence and overall survival in patients with completely resected NSCLC who received adjuvant chemotherapy and in those who did not. Patients and methods: A retrospective cohort study was conducted in 247 patients with completely resected NSCLC. All patients had been treated with anatomic resection (lobectomy or pneumonectomy) with systematic mediastinal lymphadenectomy between January 2002 and December 2011 at Chiang Mai University Hospital, Chiang Mai, Thailand. They were divided into two groups: recurrence and no recurrence. Protein expression of ERCC1 and RRM1 was determined by immunohistochemistry. Correlations between clinicopathologic variables, including ERCC1 and RRM1 expression and tumor recurrence, were analyzed. Univariate and multivariate Cox proportional hazards regression analysis stratified by nodal involvement, tumor staging, intratumoral blood vessel invasion, intratumoral lymphatic invasion, and tumor necrosis was used to identify the prognostic roles of ERCC1 and RRM1. Results: ERCC1 and RRM1 expression did not demonstrate prognostic value for tumor recurrence and overall survival in patients with completely resected NSCLC. In patients who did not receive adjuvant chemotherapy treatment, those with high ERCC1 and high RRM1 expression seemed to have greater potential for tumor recurrence and shorter overall survival than did those who had low ERCC1 and low RRM1 (hazard ratio [HR] =1.7, 95% confidence interval [CI] =0.6-4.3, P=0.292 and HR =1.6, 95% CI =0.5-4.5, P=0.411, respectively). In contrast, in patients who received adjuvant chemotherapy treatment, those with high ERCC1 and high RRM1 expression seemed to have benefited from adjuvant chemotherapy and showed good overall survival compared with those who had low ERCC1 and low RRM1 (HR =0.8, 95% CI = 0.4-1.8, P=0.612 and HR = 0.4, 95% CI = 0.1-2.4, P=0.325, respectively). Subgroup analysis in patients whose first-line metastatic chemotherapy failed demonstrated that ERCC1 expression and RRM1 expression were not prognostic factors for tumor recurrence and overall survival; however, patients who had high ERCC1 and high RRM1 expression seemed to have benefited from first-line chemotherapy treatment (HR =0.7, 95% CI =0.3-1.8, P=0.458). Conclusion: ERCC1 expression and RRM1 expression were not prognostic of tumor recurrence and overall survival in patients with completely resected NSCLC, either with or without adjuvant chemotherapy. Prospective studies that include a larger number of patients are needed for definite conclusions. © 2013 Tantraworasin et al.